2011
DOI: 10.5402/2011/502987
|View full text |Cite
|
Sign up to set email alerts
|

Joint Scheme for Physical Layer Error Correction and Security

Abstract: We present a joint scheme that combines both error correction and security at the physical layer. In conventional communication systems, error correction is carried out at the physical layer while data security is performed at an upper layer. As a result, these steps are done as separate steps. However there has been a lot of interest in providing security at the physical layer. As a result, as opposed to the conventional system, we present a scheme that combines error correction and data security as one unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…This physical layer encryption scheme provides the conditional security even if the eavesdropper channel is the same or better than the main channel. Several physical layer encryption schemes were proposed in which cryptography and channel coding are combined in a single step [9][10][11][12][13][14]. It is shown that these schemes are capable of providing data reliability, secrecy and integrity.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…This physical layer encryption scheme provides the conditional security even if the eavesdropper channel is the same or better than the main channel. Several physical layer encryption schemes were proposed in which cryptography and channel coding are combined in a single step [9][10][11][12][13][14]. It is shown that these schemes are capable of providing data reliability, secrecy and integrity.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we discuss the advantages of the proposed scheme compared with the previously proposed physical layer encryption schemes [3][4][5][6][7][8][9][10][11][12][13][14] in terms of computational complexity, key size and security.…”
Section: Comparison With the Other Physical Layer Encryption Schemesmentioning
confidence: 99%
See 3 more Smart Citations